DEVELOPMENT OF WORK AND ENERGY ASSESSMENT WITH EVIDENCE-CENTERED DESIGN APPROACH - Novieyanti, Armelya; Sirait, Judyanto; Habellia, Ray Cinthya; Sulaiman, Naim (Journal of Teaching and Learning Physics, 2025)
The purpose of this study is to develop work and energy assessment with an Evidence-Centered Design (ECD) approach. ECD is a framework of thinking that focuses on evidence of learners' abilities. ECD has three main components which are claims, evidence, and questions. Competencies in the assessment using Scientific Practices consist of the ability to use and develop representations, analyze and interpret data, explain arguments accompanied by evidence, and evaluate information. The development model used is Research and Development (R&D) with stages: analysis, design, development, implementation, and evaluation. These assessments are validated by validators and analyzed using Aiken indexes. The validation results showed a very high validity value of 0.87. Then, this assessment is carried out in one-to-one tests and small-scale trials. Based on the results of validation and trial of this assessment, it is suitable to be used by teachers as a guideline in compiling assessments.